“Don’t Forget the Whistle”: Novice Physical Education Teachers’ Reflections on Their Beliefs, Teaching Practices, and Identities - Muhammad Hamid Anwar; Herka Maya Jatmika; Caly Setiawan (Education Sciences)
The purpose of the current study was to investigate novice PE teachers’ reflections regarding beliefs and how they played out in teaching practices and identity formation within the settings of their profession. We recruited 31 PE teachers in their early careers to participate in this study. Data were collected through their written accounts of their reflection and in-depth interviews. Analysis of the collected data followed the procedures of thematic analysis through which reflexivity had been emphasized during the analysis process. The results showed three constructed themes. These were teachers’ reflections on their beliefs, PE teaching practices, and PE teachers’ professional identities. We conclude that PE teachers’ reflections on belief systems, as well as the purpose of the subject, have, in one way or another, shaped practices and professional identities. Teachers take up contemporary discourse regarding education, which is not fully aligned with available professional development programs that effectively improve the practices. Teachers form, maintain, and negotiate their professional identities in relation to their beliefs and their actual practices.